2008
DOI: 10.1007/s12028-008-9085-8
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Blood Pressure Reduction in Acute Intracerebral Hemorrhage: Feasibility and Safety

Abstract: A more aggressive reduction of acute hypertension after ICH does not increase the rate of neurological deterioration even when treatment is initiated within hours of symptom onset. Lowering BP aggressively did not affect hematoma and edema expansion but this possibility deserves further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 31 publications
3
45
0
1
Order By: Relevance
“…Although only 50% of our patients achieved a target MAP of 100 -110 mm Hg using our pre-specified goal of 120 min, over 90% of our patients reached this goal with an additional 80 min of therapy. A prior study by Koch et al has shown that the MAP can be safely lowered to a level of Ͻ 110 mm Hg in patients with spontaneous ICH (20). The average time to target MAP in our study compares favorably to this study (123 min Ϯ 73 min compared to 163 min Ϯ 164 min in the Koch et al study) (20).…”
Section: Discussionsupporting
confidence: 66%
“…Although only 50% of our patients achieved a target MAP of 100 -110 mm Hg using our pre-specified goal of 120 min, over 90% of our patients reached this goal with an additional 80 min of therapy. A prior study by Koch et al has shown that the MAP can be safely lowered to a level of Ͻ 110 mm Hg in patients with spontaneous ICH (20). The average time to target MAP in our study compares favorably to this study (123 min Ϯ 73 min compared to 163 min Ϯ 164 min in the Koch et al study) (20).…”
Section: Discussionsupporting
confidence: 66%
“…Details of the studies and participants are given in Table 1 and online supplementary Table e-1, respectively. All trials used adequate methods of sequence generation and allocation concealment except one [7]. All studies were rated as high risk of performance and low risk of detection, attrition, and reporting bias (online suppl.…”
Section: Resultsmentioning
confidence: 99%
“…3,4 Several recent trials have sought to determine whether intensive lowering of BP acutely improves outcomes in patients with ICH. [5][6][7][8][9][10] Over the last several years, a growing number of studies have characterized the presence and frequency of ischemic lesions remote from the acute hematoma visualized on diffusion-weighted imaging (DWI) in patients with primary ICH undergoing MRI. [11][12][13][14][15][16][17][18][19] Across these series, remote DWI lesions are visualized in 11%-41% of patients.…”
mentioning
confidence: 99%